A new proof-of-work mechanism for bitcoin - Ning Shi (Financial Innovation, 2016)
Background: Bitcoin system, when more than 51% computing power is controlled by a single node, the block chain can be distorted maliciously. This is called 51% attack which is a well-known potential risk that could destroy the Bitcoin system. Method: The paper proves that under the current proof-of-work mechanism, computing power eventually will be centralized at a single node if miners are rational enough. Result: The paper propose a new proof-of-work mechanism that improves decentralization and reduces the risk of 51% attack without increasing the risk of Sybil attack. Concusions: This new mechanism introduces a series of principles such as Career open to all talents, without distinction of birth, Distribution according to labor and All Men are created equal.
Keywords: 650; Digital currency; Consensus mechanism; Bitcoin; proof-of-work